2017
DOI: 10.1038/s41467-017-02351-0
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphatase SHP2 negatively regulates NLRP3 inflammasome activation via ANT1-dependent mitochondrial homeostasis

Abstract: Aberrant activation of NLRP3 inflammasome has an important function in the pathogenesis of various inflammatory diseases. Although many components and mediators of inflammasome activation have been identified, how NLRP3 inflammasome is regulated to prevent excessive inflammation is unclear. Here we show NLRP3 inflammasome stimulators trigger Src homology-2 domain containing protein tyrosine phosphatase-2 (SHP2) translocation to the mitochondria, to interact with and dephosphorylate adenine nucleotide transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 47 publications
(46 reference statements)
1
73
1
Order By: Relevance
“…Our findings provide a better understanding of MDSCs accumulation and activation by tumor cells and its contribution to lung cancer development. Previous studies have proved a complex process for MDSCs accumulation and activation, including two groups of signals . One is for the expansion of immature myeloid cells, such as GM‐CSF and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide a better understanding of MDSCs accumulation and activation by tumor cells and its contribution to lung cancer development. Previous studies have proved a complex process for MDSCs accumulation and activation, including two groups of signals . One is for the expansion of immature myeloid cells, such as GM‐CSF and STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al . recently reported that ANT1 regulated the NLRP3 inflammasome in macrophages . Therefore, in addition to the inflammasome, we hypothesized that ANT1 also regulates inflammatory cytokine expression.…”
Section: Resultsmentioning
confidence: 92%
“…These results suggest that ANT1 knockdown has little influence on cell viability of macrophages. Previous work has shown that ANT1 regulates the inflammasome [13]. We hypothesized that ANT1 regulated not only the inflammasome but also cytokine expression.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations